(untitled) (CIPEEX, 2022)
ACCESSIBILITYANDINCLUSIONSHOULDBEDISCUSSED IN SOCIAL, LEGAL, EDUCATIONAL, COMMUNICATIVE, ARCHITECTURAL, AMONGOTHERS, AIMINGATTHEADAPTATIONOFTHEENVIRONMENTTOALLHUMANDIVERSITYANDPROMOTIONOFAUTONOMY. THE PURPOSEOFTHISPAPERISTOUNITE 5 CASE REPORTSOFPEOPLEWHOHAVE A DISABILITYANDTOPRESENTTHROUGHPOSTERS, PARTOFTHELIFEEXPERIENCEANDTHEDIFFICULTIESFACEDBYTHEM. THE PURPOSEOFTHISPAPERISTOINFORMTHEACADEMICCOMMUNITY, FACULTYANDSOCIETYABOUTTHEIMPORTANCEOFOTHERNESSANDPROMOTEAWARENESSABOUTTHENEED FOR CHANGES FOR INTEGRATIONANDTO BREAK WITHPSYCHOLOGICALANDATTITUDINALBARRIERS. THE WORKWILLBEPRODUCED IN WHITECARTOLINES, MANUALLY, THESEWILLBEEXPOSED, TRAPPEDBYPREACHERS IN STRINGSOFSTRINGS. EACHCARDWILLPRESENTTHEPARTICIPANT’S FULL NAME, A PHOTOANDHIS INDIVIDUAL REPORT, FOLLOWING A SIMPLESTANDARDIZATION, WHICHWILLBEPROMOTEDTHROUGH A QUESTIONNAIRE. ALLREPORTSWEREAUTHORIZEDBYTHEPARTICIPANTSTHROUGH A FREEANDINFORMEDCONSENTFORM, ANDALLAGREEDTOPARTICIPATE IN ANDEXPOSETHEREPORTANDPHOTOS IN THE CULTURAL SHOW OFTHEUNIEVANGELICA 2018 DENTISTRYCOURSE. IN ADDITION, CARDSWILLBEINSERTEDWITHINFORMATIONALPHRASESANDIMPACTFULONTHESUBJECT. IN TOTAL, 15 CARDSWILLBEPRODUCED. KEYWORDS: CASE REPORT. DEFICIENCY. ALTERITY.